Indianness and Organisation Development. Issue 3 (July 2020) - Malhotra, Ashok
Anglo-Saxon notions, when deployed in societies like those in India, often become a source of stress and tension, causing waste of human energy and potential. This article traces Indian civilisational predispositions and their uneasy relationship with the prevailing corporate imperatives, exploring these as problematics in the action world of organisations and also as opportunities that need managerial attention in such a context. The author acknowledges the nuances that stem from civilisational uniqueness and underpins it in Indian diversity of contexts and major discontinuities in its geopolitical history. Implications for the organisation development (OD) practitioner in Indian context follow from this unique analytical frame.